The Effects of Educational-Occupational Mismatch on Immigrant Earnings in Australia, with International Comparisons - Chiswick, B.; Miller, Paul (Wiley-Blackwell, 2010)
This paper examines the way immigrant earnings are determined in Australia. It uses the overeducation/required education/undereducation framework and a decomposition of the native-born/foreign-born differential in the payoff to schooling. This decomposition links overeducation to the less-than-perfect international transferability of immigrants’ human capital, and undereducation to favorable selection in immigration. Comparisons are offered with findings from analyses for the U.S. and Canada to enable assessment of the relative impacts of favorable selection and the limited international transferability of human capital to the lower payoff to schooling for the foreign born. The sensitivity of the results of the decomposition to several measurement issues is assessed.